Education And Training On Non-Pharmacological Management Of Rheumatic Pain In Jalan Gedang Village - Khanesia Azara Sapitri; Mirna Anita Sari; Pera Sapitri; Putri Rahayu; Wilia Mayasari; Retni Retni (Universitas Dehasen Bengkulu, 2026)
Rheumatic diseases, encompassing conditions like Rheumatoid Arthritis (RA) and other chronic musculoskeletal disorders, represent a leading global health concern and a primary contributor to non-fatal disability. Globally, the prevalence of disability due to musculoskeletal disorders is projected to increase by up to 115% between 2020 and 2050. The objective of this service is to improve the community's (elderly) ability and skills in managing rheumatic symptoms non- pharmacologically. The method used was an educational intervention and practical training over 2 weeks at the RT 08 Security Post (Poskambling). The main interventions included: Rheumatism Counseling, Range of Motion (ROM) Exercise training, and Education on Warm Compresses for pain. The activity was attended by 30 elderly participants. The results showed a significant increase in participants' knowledge scores and a proven decrease in the average pain scale after the intervention. This program is effective for improving knowledge and providing practical skills in community rheumatic pain management.